THE APPLICATION OF INTERVAL TRAINING ON THE ENDURANCE OF EXTRACURRICULAR BADMINTON PARTICIPANTS AT SRIMULYO STATE JUNIOR HIGH SCHOOL. - Adellia Putri Lestari; Ever Sovensi; Doni Atmanegara (Journal of Sport Science and Tourism Activity, 2026)
This study aims to determine the effect of the application of interval training on the endurance of extracurricular badminton participants at SMP Negeri Srimulyo. This study uses a quantitative method with an experimental design in the form of one group pre-test post-test. The research sample amounted to 16 extracurricular participants of men's badminton who were selected using saturated sampling techniques. The data collection technique was carried out through endurance tests using a bleep-test. The results showed a significant increase in endurance, as shown by the average pre-test score of 28.48 increased to 32.48 in the post-test. The results of the hypothesis test using the t-test showed that the tcount > ttable (9.693 >2.131) with a significance value of 0.001< 0.05, so that Hα was accepted. This proves that the interval training method is effective in increasing the endurance of extracurricular badminton participants. Thus, this method can be used as an alternative to simple, effective and easy to apply in training to improve the performance of extracurricular participants.